Ngu-Vi-Tieu-Khat decoction, a Vietnamese traditional medicine, possesses hypoglycemic and hypolipidemic effects on streptozotocin-induced type-2 diabetic rat model - Minh Hoang Le; Huyen Sanh Sam; Duy Toan Pham; Ngoc Chi Lan Nguyen; Ngoc Diem Le; Tran Nhat Phong Dao (Pharmacia, 2023)
This study aims to assess the hypoglycemic effects of Ngu-Vi-Tieu-Khat (NVTK) decoction, a traditional Vietnamese medicine, in a rat model of type-2 diabetes. The NVTK decoction was prepared using the maceration method and tested for its hypoglycemic effects by measuring blood glucose levels, insulin resistance indicators, and pancreatic mass. The results showed that NVTK decoction improved diabetes symptoms, increased insulin levels, reduced insulin resistance, restored pancreatic mass, and decreased total cholesterol (TC), triglycerides (TG) and low-density lipoprotein cholesterol (LDL-C) while increasing high-density lipoprotein cholesterol (HDL-C). The hypoglycemic effects of NVTK were comparable to those of gliclazide at a dose of 10 mg/kg. In conclusion, NVTK decoction possesses hypoglycemic properties and could be explored as a potential traditional medicine for treating type-2 diabetes in humans.